Teknologi Pembenihan Abalon Haliotis squamata Untuk Meningkatkan Produksi Budidaya Secara Berkelanjutan - Andri Iskandar; AB Jannar; A Sujangka; Muslim Muslim (Samakia : Jurnal Ilmu Perikanan, 2022)
Abalone has a specific taste, containing 71,99% protein; 3,2% lipid; 5,6% crude fiber; and 0,6% water. The selling price in the domestic market ranges from IDR 250.000-IDR 600.000 per kg depending on the size and in the international market it ranges from USD 22-USD 66 per kg depending on the quality and type. The hatchery activities begin with rearing broodstock until the gonads mature. It was placed in plastic crates with a density of 40-50 individuals/unit and fed with macroalgae. The parent which is ready to be spawned has developed gonad and covers the hepatopancreas organ over 50%, and carried out on a spawning container. Larvae rearing begins with a container that has been cultured with benthic diatom as the larvae feed. Abalone measuring 1-2 cm was harvested and transferred to seed maintenance containers. Seed maintenance was carried out for 2-3 months and produces abalone seeds ready for sale with a size of 3cm. Hatchery activities produce FR 60%, HR 85%, and SR 0,1-1%. Seed packaging was carried out using three stage, a net bag with a density of 75-100 individuals/bag, a plastic bag filled with 20 net bags/plastic sheet, and a styrofoam box filled with 1 plastic/box.